THE EFFECT OF BLACK POLYETHYLENE MULCH ON YIELD OF FIELD-GROWN CUCUMBER - Tomasz Spiżewski; Barbara Frąszczak; Alina Kałużewicz; Włodzimierz Krzesiński; Jolanta Lisiecka (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
Cucumber is one of the most popular vegetables in Poland. This vegetable species is characterised by high requirements in terms of soil temperature and moisture. The utilization of polyethylene mulch in combination with drip irrigation has played a major role in the increases in production of cucumber. The benefits associated with the use of this cultivation method include earlier and higher yields, reduced soil evaporation, reduced weed populations, reduced fertilizer leaching, greater water use efficiency, reduced soil compaction, control of certain pests, and cleaner harvested product. In years 2002, 2003 and 2005 experiments were conducted to study the impact of soil mulching with black polyethylene on Akord F1 cucumber yields. Plants were cultivated on sandy loam soil using irrigation and fertigation applied with the assistance of drip lines. No significant differences were observed in levels of total and marketable yields of fruits as well as in dry matter and total carbohydrate contents in fruits obtained from plants cultivated in mulched and unmulched soils. Irrigation efficiency, on the soil mulched with black polyethylene was higher than on the soil without mulching.